(untitled) (International Journal of Pharmaceutical and Life Sciences, 2013)
The Ardisia colorata is one of the rare hill-tract plants in Bangladesh. The experimental research was intended to evaluate the phytochemical and antimicrobial activity of 70% ethanolic extract of leaves and bark of Ardisia colorata. Preliminary phytochemical screening of both the leaf and bark extract revealed the presence of various classes of compounds such as saponins, reducing sugars, tannins, and terpenoids with minor presence of alkaloid and flavonoid. When antimicrobial study was carried out against 10 different strains of microorganisms by detecting the zone of inhibition with disc diffusion technique, the two extracts showed very strong effect especially against Vibrio parahemolyticus and Bacillus subtilis with trace activity against Salmonella typhi. When further quantitative estimation was carried out using Minimum Inhibitory Concentration (MIC) with alternate methodology involving incorporation of phenol red indicator, their corresponding MIC numerical values were deduced at 3mg/ml respectively. DOI: http://dx.doi.org/10.3329/ijpls.v2i4.17115 International Journal of Pharmaceutical and Life Sciences Volume 2, Issue 4: October 2013; 158-164